Productivity loss due to overweight and obesity: a systematic review of indirect costs - Göttler, Andrea; Große, Anna; Sonntag, Diana (BMJ open, 2017)
Objective: The increasingly high levels of overweight and obesity among the workforce are accompanied by a hidden cost burden due to losses in productivity. This study reviews the extent of indirect cost of overweight and obesity. Methods: A systematic search was conducted in eight electronic databases (PubMed, Cochrane Library, Web of Science Core Collection, PsychInfo, Cinahl, EconLit and ClinicalTrial.gov). Additional studies were added from reference lists of original studies and reviews. Studies were eligible if they were published between January 2000 and June 2017 and included monetary estimates of indirect costs of overweight and obesity. The authors reviewed studies independently and assessed their quality. Results: Of the 3626 search results, 50 studies met the inclusion criteria. A narrative synthesis of the reviewed studies revealed substantial costs due to lost productivity among workers with obesity. Especially absenteeism and presenteeism contribute to high indirect costs. However, the methodologies and results vary greatly, especially regarding the cost of overweight, which was even associated with lower indirect costs than normal weight in three studies. Conclusion: The evidence predominantly confirms substantial short-term and long-term indirect costs of overweight and obesity in the absence of effective customised prevention programmes and thus demonstrates the extent of the burden of obesity beyond the healthcare sector.